Statins for Primary Prevention in Older Adults—Moving Toward Evidence‐Based Decision‐Making. Issue 11 (2nd October 2018) - Singh, Sonal; Zieman, Susan; Go, Alan S.; Fortmann, Stephen P.; Wenger, Nanette K.; Fleg, Jerome L.; Radziszewska, Barbara; Stone, Neil J.; Zoungas, Sophia; Gurwitz, Jerry H.
Abstract : Objectives: To determine the efficacy and safety of statins for primary prevention of atherosclerotic cardiovascular disease (ASCVD) events in older adults, especially those aged 80 and older and with multimorbidity. Methods: The National Institute on Aging and the National Heart, Lung and Blood Institute convened A multidisciplinary expert panel from July 31 to August 1, 2017, to review existing evidence, identify knowledge gaps, and consider whether statin safety and efficacy data in persons aged 75 and older without ASCVD are sufficient; whether existing data can inform the feasibility, design, and implementation of future statin trials in older adults; and clinical trial options and designs to address knowledge gaps. This article summarizes the presentations and discussions at that workshop. Results: There is insufficient evidence regarding the benefits and harms of statins in older adults, especially those with concomitant frailty, polypharmacy, comorbidities, and cognitive impairment; a lack of tools to assess ASCVD risk in those aged 80 and older; and a paucity of evidence of the effect of statins on outcomes of importance to older adults, such as statin‐associated muscle symptoms, cognitive function, and incident diabetes mellitus. Prospective, traditional, placebo‐controlled, randomized clinical trials (RCTs) and pragmatic RCTs seem to be suitable options to address these critical knowledge gaps. Future trials have to consider greater representation of very old adults, women, underrepresented minorities, and individuals of differing health, cognitive, socioeconomic, and educational backgrounds. Feasibility analyses from existing large healthcare networks confirm appropriate power for death and cardiovascular outcomes for future RCTs in this area. Conclusion: Existing data cannot address uncertainties about the benefits and harms of statins for primary ASCVD prevention in adults aged 75 and older, especially those with comorbidities, frailty, and cognitive impairment. Evidence from 1 or more RCTs could address these important knowledge gaps to inform person‐centered decision‐making.J Am Geriatr Soc 66:2188–2196, 2018.